SALURAN PEMASARAN PRODUK SUSU KAMBING PADA PT. SEIDERAS AGROFARM DESA RAMBAH TENGAH BARAT KECAMATAN RAMBAH - Sunarti, Wiwik; Defidelwina; Febriani Yamesa Away, Siska (SUNGKAI, 2023)
This research was conducted to determine the marketing function, marketing channels, margins, profit ratios, farmer's share and marketing efficiency. The research method used is the case study method. Data were obtained through direct observation to the research site and interviews. The sampling technique used is snowball sampling. The data is analyzed discriptively. The results of the study suggest that PT. Seideras Agrofarm has performed marketing functions as evidenced by the existence of exchange functions, physical functions and facility functions. There are six marketing channels with the most efficient marketing channels found in marketing channel V, namely producers – wholesalers B – consumers with a marketing margin of 60%, profit ratio of 2.23, farmer's share of 40%, and efficient of 30.95%.